Assessing the Feasibility of Typhoid Elimination. (29th July 2020) - Stanaway, Jeffrey D; Atuhebwe, Phionah L; Luby, Stephen P; Crump, John A
Abstract: In 1993, the International Task Force on Disease Eradication classified the political will for typhoid eradication as "none." Here we revisit the Task Force's assessment in light of developments in typhoid vaccines and increasing antimicrobial resistance in Salmonella Typhi that have served to increase interest in typhoid elimination. Considering the requisite biological and technical factors for elimination, effective interventions exist for typhoid, and humans are the organism's only known reservoir. Improvements in water supply, sanitation, hygiene, and food safety are critical for robust long-term typhoid control, and the recent Strategic Advisory Group of Experts on Immunization recommendation and World Health Organization prequalification should make typhoid conjugate vaccine more accessible and affordable in low-income countries, which will allow the vaccine to offer a critical bridge to quickly reduce burden. While these developments are encouraging, all current typhoid diagnostics are inadequate, having either poor performance characteristics, limited scalability, or both. No clear solution exists, and this should be viewed as a critical challenge to any elimination effort. Moreover, asymptomatic carriers and limited data and surveillance remain major challenges, and countries considering elimination campaigns will need to develop strategies to identify high-risk populations and to monitor progress over time. Finally, policymakers must be realistic in planning, learn from the planning failures of previous elimination and eradication efforts, and expect unforeseeable shocks and setbacks. In the end, if we assume neither unanticipated breakthroughs in typhoid control nor any chaotic shocks, history suggests that we should expect typhoid elimination to take decades.